Thiopentone versus propofol-anaesthetic of choice in patients undergoing modified electroconvulsive therapy - Peter, Vigil; Mathew, Sumesh; Thomas, Tom (International Journal of Research in Medical Sciences, 2017)
Background: The use of electroconvulsive therapy (ECT) as a treatment modality has increased over the recent years. This is largely due to the use of general anaesthetics, which reduces the physical and psychological trauma associated with the procedure. We attempted to compare the hemodynamic variations and recovery characteristics, along with their effect on seizure quality in patients induced with Thiopentone /Propofol, for Modified ECT. Methods: This was a prospective, randomised controlled study, involving 80 patients. Patients in group 1 received Thiopentone 5 mg/kg, while patients in group 2 received Propofol 1 mg/kg. The hemodynamic status and recovery status were monitored in both the groups for the first thirty minutes. Seizural duration were also recorded. Data was analysed using Students t-test and Pearson Chi-square test. Results: The induction time as well as recovery time was found to be significantly lesser (p <0.05) in the propofol group. The hemodynamic response to was blunted and returned to baseline levels within 10-15 minutes after ECT in the propofol group, whereas it persisted even after 30 minutes in the thiopentone group. There was however, no significant difference in the duration of the seizural activity(p> 0.05). Conclusions: The quick and smooth induction, transient changes in hemodynamics, rapid recovery profile and minimal effects on the seizure quality altogether makes Propofol the preferred anaesthetic agent in Modified ECT.